2000
DOI: 10.1103/physrevlett.84.5451
|View full text |Cite
|
Sign up to set email alerts
|

Optical Deformability of Soft Biological Dielectrics

Abstract: Two counterpropagating laser beams were used to significantly stretch soft dielectrics such as cells. The deforming forces act on the surface between the object and the surrounding medium and are considerably higher than the trapping forces on the object. Radiation damage is avoided since a double-beam trap does not require focusing for stable trapping. Ray optics was used to describe the stress profile on the surface of the trapped object. Measuring the total forces and deformations of well-defined elastic ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
229
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(239 citation statements)
references
References 16 publications
9
229
0
Order By: Relevance
“…This concept was used to deform and measure the stress profiles of erythrocytes, which led to the development of the first optical stretcher device reported in 2000. 66 The setup was then demonstrated to stretch BALB 3T3 fibroblasts and measure their viscoelastic properties. 67 A typical optical stretcher system consists of a microchannel for loading cells into the testing region and two laser fibers located on the sides of the passageway (see Fig.…”
Section: Optical Stretchermentioning
confidence: 99%
“…This concept was used to deform and measure the stress profiles of erythrocytes, which led to the development of the first optical stretcher device reported in 2000. 66 The setup was then demonstrated to stretch BALB 3T3 fibroblasts and measure their viscoelastic properties. 67 A typical optical stretcher system consists of a microchannel for loading cells into the testing region and two laser fibers located on the sides of the passageway (see Fig.…”
Section: Optical Stretchermentioning
confidence: 99%
“…Several of the techniques for investigating cellular mechanics [12][13][14] make use of optical trapping techniques. For example, Guck and coworkers showed that single cells can be stretched by strong optical forces [15,16] …”
Section: Introductionmentioning
confidence: 99%
“…Compared to optical dynamometry using a beam-trapped bead as a probe [51], these experiments show that the main interests in using radiation pressure are the strong localization of excitation as well as its contactless character. In the meantime, Käs' group patented a new tool, called "Optical Stretcher", to probe the elasticity of red blood cells using the radiation pressure [52]. Due to its sensitivity, one of the ultimate goals of this technique is to differentiate healthy from malignancy cells from the difference in elastic response [53,54].…”
Section: Mechanical Aspectsmentioning
confidence: 99%